2022
DOI: 10.1002/ccr3.6322
|View full text |Cite
|
Sign up to set email alerts
|

Uterine malignant leiomyosarcoma associated with high levels of serum beta‐human chorionic gonadotropin: A case report

Abstract: We present the case of a 54-year-old woman diagnosed with uterine leiomyosarcoma that produced beta-human chorionic gonadotropin (β-hCG), evident by both serum and immunohistologic examination. Based on this and similar cases from the available literature, β-hCG-producing sarcomas tend to have poorer prognosis, indicating that β-hCG could potentially be used as a marker of disease status and response to the therapy; however, this association is inconsistent and should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
3
2
Order By: Relevance
“…There are also conflicting reports with regard to the role of β-hCG as a prognostic biomarker. Previous studies have reported that in some sarcoma cases β-hCG persisted postoperatively 21. In our case, serum β-hCG returned to normal after resection of the primary sarcoma, despite the presence of oligometastatic disease, therefore, this may not be representative of disease activity.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…There are also conflicting reports with regard to the role of β-hCG as a prognostic biomarker. Previous studies have reported that in some sarcoma cases β-hCG persisted postoperatively 21. In our case, serum β-hCG returned to normal after resection of the primary sarcoma, despite the presence of oligometastatic disease, therefore, this may not be representative of disease activity.…”
Section: Discussioncontrasting
confidence: 58%
“…This is somewhat consistent with our case, as our patient had evidence of oligometastatic spread. However, in our case, β-hCG returned to normal even in the presence of oligometastatic disease, suggesting that it may not be a predictor of the sarcoma’s biological behaviour 21 25. There are also conflicting reports with regard to the role of β-hCG as a prognostic biomarker.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In extra-uterine cases, elevated β-hCG was described in retroperitoneal leiomyosarcoma [18,20,21], spermatic cord leiomyosarcoma [22,23], and leiomyosarcoma of the small bowel [24]. To our knowledge, our case is the fourth in literature to describe a case of uterine leiomyosarcoma associated with elevated β-hCG [25][26][27]. What is special about this case was that the initial β-hCG levels were within normal levels, which then showed β-hCG elevation in asso-ciation with the metastatic disease, flare up and resistance to chemotherapy, and palliative radiotherapy, suggesting that β-hCG can potentially play a prognostic role in such patients.…”
Section: Discussionmentioning
confidence: 61%